A detailed study of thermal degradation of poly(2-hydroxyethyl methacrylate) - Demirelli, K; Coskun, M; Kaya, E (Elsevier Sci Ltd, 2001)
The thermal degradation behaviour of poly-2-hydroxyethyl methachrylate and of its deuterium derivative have been studied using thermogravimetry under nitrogen atmosphere, with programmed heating at 10 degreesC/min. At first, the partially degraded polymer has been examined by IR. The cold ring fraction (CRF) was trapped at two ranges from ambient temperature to 340 degreesC and 340-400 degreesC. These CRFs were characterized by IR, H-1, C-13 NMR, and GC-MS. When the polymer decomposes thermally at two temperature ranges which are from ambient temperature to 340 degreesC and 340-400 degreesC, at both CRFs, the major product is monomer due to depolymerisation reaction. The side products arising from ester decomposition are a six-membered glutaric anhydride type of ring, an oxolane type of ring, 2-isopropenyl ethyl methacrylate, methacrylic acid and CO2. A mechanism which accounts for all these products has been formulated. The activation energy for the thermal degradation of poly(HEMA) is predicted as 129.8 kJ/mol (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: thermal degradation; HEMA